EEG characteristics in depression "negative" and "positive" schizophrenia - Begić, Dražen; Mahnik-Miloš, Mirta; Grubišin, Jasmina (2009)
qEEG investigations present differences in the comparison of schizophrenic patients and healthy examinees, as well as of depressive patients and healthy controls. The comparison of "positive" and "negative" schizophrenia also presents differences in the qEEG parameters. Changes in qEEG are various in these studies, but not always consistent. In this research we wanted to compare "positive" schizophrenia, "negative" schizophrenia and depression. Subjects and methods: The sample comprised 55 examinees (all women): 20 patients with "positive" schizophrenia, 15 patients with "negative" schizophrenia and 20 patients with depression. The standard EEG registration was done in all of them. From the recorded material, the 20-second period without artifacts was analyzed by the FFT method.qEEG parameters differ in the comparison of "positive" and "negative" types of schizophrenia. These differences are more numerous and more significant than those obtained in the comparison of each of these types of schizophrenia with depression
4th Croatian congress on psychopharmacotherapy with international participation, Zadar, October 7-10, 2009
Bibliografija: 23 jed
Keywords: Shizofrenija -- Depresija -- EEG -- Beta-aktivnost -- Delta-aktivnost